Theoretical study of the boot process steeply inclined conveyor - Repin S.V.; Aleinik V.I.; Bazhenov A.A. (Научно-технический вестник Брянского государственного университета)
Conveyor transport is widely used in various sectors of the economy. Very common are conveyors designed to move bulk cargo at significant angles of transportation, the so-called steeply inclined conveyors. At the same time, the theoretical aspects of the work have been studied relatively poorly, which does not allow to rely on previously accumulated knowledge in the design of new designs of steep-sided transporting machines. This leads to the fact that the characteristics of the conveyor in its design are selected very approximately, without careful theoretical calculation. This, in turn, leads to irrational use of resources, both in the construction of new conveyors and in the operation of existing ones. This article presents a theoretical calculation of the loading unit of the conveyor, in particular, the behavior of the load when loading the conveyor As a result of the formula for calculating the speed of the load on the conveyor belt, as well as the speed of its sliding on the loading device in different areas depending on its geometric parameters. Programs were also compiled to calculate these speeds at its various geometric parameters. The influence of geometric parameters of the feeder on the behavior of the load is analyzed. The mathematical model of the granular medium behavior is given.